Exploring the Influence of Mental Workload on Performance Factors: A Case Study in Education - Bariyah, Choirul; Oktafiandi, Fikram; Budijati, Siti Mahsanah (The Indonesian Institute of Science and Technology Research, 2024)
Amid the COVID-19 pandemic, educational institutions in Indonesia, including vocational schools in Bontang, adopted remote learning policies to continue education. Surveys and interviews conducted with teachers at a vocational school revealed signs of stress, including quick temper, continuous mistakes in tasks, and forgetfulness. This study seeks to assess the level of mental workload, teacher performance, and the impact of mental workload factors on the performance of vocational teachers during the COVID-19 pandemic. Teacher performance is the dependent variable, while mental workload is the independent variable. Mental workload dimensions measured include time pressure, mental effort, and psychological stress, whereas teacher performance has work quality, accuracy/speed of work, initiative in work, workability, and communication. The study involved a sample of 20 teachers from a vocational school. Data analysis utilized simple linear regression processed using SPSS software. Subjective assessments of mental workload by teachers indicated that the highest proportion was the need for increased concentration during teaching activities. Regarding teacher performance, the highest ratios were associated with mastering teaching materials, managing the teaching-learning process, and leading the class during the COVID-19 pandemic. The simple linear regression testing results revealed a low influence of the existing mental workload on teachers' performance. The R square value indicated that mental workload affected teacher performance by 14.7%, with the rest influenced by variables outside the regression model.